Taxonomic revision of some Micromyinae (Diptera: Cecidomyiidae) described by Zoya L. Berest - Jaschhof, Mathias (Zootaxa, 2016)
The taxonomy of 13 Micromyinae (Cecidomyiidae) described by Zoya L. Berest in 1986–2001 is revised. As a result, 12 new junior subjective synonyms are proposed: Aprionus giganteus Berest, 1991 syn. nov. of Aprionus halteratus (Zetterstedt, 1852); Aprionus lobatus Berest, 1986 syn. nov. of Aprionus acutus Edwards, 1938; Aprionus onychophorus Berest, 1991 syn. nov. of Aprionus cardiophorus Mamaev, 1963; Bryomyia multispinata Berest, 1988 syn. nov. of Bryomyia gibbosa (Felt, 1907); Cordylomyia barsovi Berest, 1991 syn. nov. of Neurolyga fenestralis Rondani, 1840; Eleniella Berest, 2001 syn. nov. of Monardia Kieffer, 1895; Eleniella kyseluci Berest, 2001 syn. nov. of Monardia obsoleta Edwards, 1938; Heterogenella dolini Berest, 1989 syn. nov. of Heterogenella cambrica (Edwards, 1938); Peromyia almensis Berest, 1989 syn. nov. of Peromyia caricis (Kieffer, 1901); Peromyia emarginata Berest, 1988 syn. nov. of Peromyia fungicola (Kieffer, 1901); Peromyia paliformia Berest, 1994 syn. nov. of Peromyia aeratipennis (Skuse, 1888); and Peromyia podolica Berest, 1991 syn. nov. of Peromyia fungicola (Kieffer, 1901). Misinterpretation of preparation artifacts for taxonomic characters is shown to be the principal reason for the identification errors unveiled here. Peromyia extensa Berest, 1991, a valid species known only from the type specimens, is redescribed.